2015
DOI: 10.1016/j.bjhh.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated phase chronic myeloid leukemia: evaluation of clinical criteria as predictors of survival, major cytogenetic response and progression to blast phase

Abstract: BackgroundPublished criteria defining the accelerated phase in chronic myeloid leukemia are heterogeneous and little is known about predictors of poor outcome.MethodsThis is a retrospective study of 139 subjects in the accelerated phase of chronic myeloid leukemia treated with imatinib at a single center in Brazil. The objective was to identify risk factors for survival, major cytogenetic response and progression to blast phase in this population. The factors analyzed were: blasts 10–29%, basophils ≥ 20%, plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
2
4
0
1
Order By: Relevance
“…We also report that CP patients who were tolerant to their received TKIs tended to develop ACAs less (14/34, 17%) than their counterparts who were defined as intolerant to TKIs (2/6, 33%). These observations could be matched with previous studies [10], [28], [29]. An interesting observation that we report in this study is the near significance higher median OS and EFS of CML-CP patients who had a shift to a different generic IM during their treatment course due to the unavailability of Glivec ® (p = 0.087 and p = 0.100, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also report that CP patients who were tolerant to their received TKIs tended to develop ACAs less (14/34, 17%) than their counterparts who were defined as intolerant to TKIs (2/6, 33%). These observations could be matched with previous studies [10], [28], [29]. An interesting observation that we report in this study is the near significance higher median OS and EFS of CML-CP patients who had a shift to a different generic IM during their treatment course due to the unavailability of Glivec ® (p = 0.087 and p = 0.100, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Patients with thrombocytopenia (<100×109/L) had a lower median OS than patients who presented with higher platelet counts (p = 0.07) and was found to be an independent poor prognostic factor in Egyptian CML patients upon the log-rank statistical test of the impact of variables on OS (p=0.082). This correlation was similar to a previously reported significant correlation between thrombocytopenia at presentation and unresponsiveness to TKI therapy and lack of MCyR which was consequently and significantly correlated with OS and EFS [28]. A higher percentage of CML-CP patients who failed to achieve optimal response to TKI therapy had ACAs (42%) compared to (28%) of optimal responders.…”
Section: Discussionsupporting
confidence: 89%
“…Early studies in AP-CML patients not previously exposed to other TKIs showed that imatinib determined 60–85% rates of complete hematologic response (CHR, 16–45% of complete cytogenetic response (CCyR) and 19–34% of major molecular response (MMR) (5660, 63). OS ranged from 74% at 12 months to around 40–50% at 5–7 years, an outcome clearly less favorable as compared to CP patients.…”
Section: The Role Of Tki In Advanced Phasementioning
confidence: 99%
“…Molecular monitoring should be performed by reverse transcriptase quantitative PCR (RT-qPCR) from total peripheral blood leucocytes using standardised methodologies that adhere to national and international guidelines (see Fig 1). 35,[37][38][39]46 Assessment by digital PCR as an alternative to RT-qPCR may increase in the future, but irrespective of the method used, results should be expressed on the International Scale (IS) 68 and indicate the molecular response (MR) level.…”
Section: Response Criteria and Monitoring Response To Therapymentioning
confidence: 99%
“…33 Studies of TKIs in advanced phase. Imatinib in de novo AP CML 46,67,86,89,144,153 and in BC. 42,87,122,141,144,149 Dasatinib and nilotinib in imatinib failure, in AP 3,34,53,82,84,117 and in BC.…”
Section: Author Contributionsmentioning
confidence: 99%